2020
DOI: 10.1177/0976747920963401
|View full text |Cite
|
Sign up to set email alerts
|

Health Status, Government Health Expenditure and Economic Growth Nexus in India: A Toda–Yamamoto Causality Approach

Abstract: This article attempts to examine the causal linkage among government health expenditure, health status and economic growth in India for the period from 1981–1982 to 2015–2016. The results of Johansen co-integration test indicate that government health expenditure, health status and economic growth have long-run relationship in India. The results of Toda–Yamamoto causality test showed that there existed unidirectional causal relationship running from government health expenditure to gross domestic product—GDP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
(16 reference statements)
0
5
1
3
Order By: Relevance
“…It is recognized that research reveals mixed results related to government spending on health but leans toward positive outcomes from increased public spending [13][14][15]. There are two common approaches used to determine the implication of government spending on public health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that research reveals mixed results related to government spending on health but leans toward positive outcomes from increased public spending [13][14][15]. There are two common approaches used to determine the implication of government spending on public health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Dampak kesehatan terhadap pertumbuhan ekonomi pada suatu negara serta hubungan antara kesehatan masyarakat dengan pertumbuhan ekonomi telah menjadi perhatian yang sangat serius bagi pembuat kebijakan maupun peneliti (Kaur, 2020). Hal tersebut semakin terlihat ketika pandemic Covid-19 melanda dunia, berdasarkan laporan World Economic Outlook yang diterbitkan oleh IMF pada tahun 2021, pertumbuhan ekonomi secara global turun -3.2% pada tahun 2020 (Sarıışık & Usta, 2021).…”
Section: Pendahuluanunclassified
“…Salah satu indikator health capital sebuah negara yang berperan penting terhadap pertumbuhan ekonomi adalah health expenditure (Canbay & Kırca, 2022). Hubungan antara pertumbuhan ekonomi dan pengeluaran terhadap kesehatan (public/private) dan dampaknya terhadap sektor kesehatan telah menjadi subjek penelitian dan perdebatan yang penting dalam beberapa tahun terakhir (Abdulqadir et al, 2022;Canbay & Kırca, 2022;Esen & Çelik Keçili, 2022;Kaur, 2020;Matahir et al, 2022;Mohapatra, 2017;Naidu & Chand, 2013;Pereira et al, 2019;Sethi et al, 2020;Wang, 2015).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Empirical work by Rahman (2008), Bhat and Jain (2006), Hooda (2015), Behera and Dash (2017) were few attempts towards evaluating the relationship of GDP and health care expenditure in Indian context. With the objective of evaluating the relationship between PEH, health status and economic growth in India for the period from 1981-1982-2016, Kaur (2020 confirmed that the GDP of the country was having unidirectional association with government expenditure in health care. While examining the impact of GDP on healthcare expenditure in Italy during 1982-2009, Fedeli (2015 showed empirical evidence in support of Wagner's law suggesting as income rises, people will choose relatively more healthcare expenditure.…”
Section: Introductionmentioning
confidence: 99%